2020
DOI: 10.3390/polym12091917
|View full text |Cite
|
Sign up to set email alerts
|

Recycling and Reprocessing of Thermoplastic Polyurethane Materials towards Nonwoven Processing

Abstract: Thermoplastic Polyurethane (TPU) is a unique tailorable material due to the interactions of hard and soft segments within the block-copolymer chain. Therefore, various products can be created out of this material. A general trend towards a circular economy with regards to sustainability in combination with TPU being comparably expensive is of high interest to recycle production as well as post-consumer wastes. A systematic study investigating the property changes of TPU is provided, focusing on two major aspec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 29 publications
2
17
0
Order By: Relevance
“…PU is a type of linear block copolymer composed of hard chain segment and soft chain segment. The hard chain segment is usually made up of carbamate groups [ 6 ], whereas the soft chain segment usually comprises polyether diols [ 7 ]. Different strength and hardness can be generated through changing the ratio of hard chain segment and soft chain segment or their structures or adding different chain extenders to exhibit the comprehensive properties [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…PU is a type of linear block copolymer composed of hard chain segment and soft chain segment. The hard chain segment is usually made up of carbamate groups [ 6 ], whereas the soft chain segment usually comprises polyether diols [ 7 ]. Different strength and hardness can be generated through changing the ratio of hard chain segment and soft chain segment or their structures or adding different chain extenders to exhibit the comprehensive properties [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…In general, heat treatment of neat TPU induced a reduction in M w caused by thermal degradation of the polymer chains. However, during the 2nd and 3rd recycling process, these values became almost unchanged, probably reaching equilibrium originating from the simultaneous degradation and accumulation of processes in the TPU 23,39 . An apparent decrease in M w and Ð, was observed for the 80 wt% composite in contrast to the TPU sample, indicating a chain shortening due to the presence of CI particles.…”
Section: Gel Permeation Chromatographymentioning
confidence: 99%
“…Vulcanized rubbers share stronger networks, a property obtained from the disulfide bonds, however they are not fit for reprocessing. The balanced properties of the TPEs originate from their microstructure, which is generated by alternating mutually immiscible soft and hard elastomeric segments with a distinctly different glass transition temperature 23 .…”
mentioning
confidence: 99%
“…As an example, a multilayer fabric containing graphene oxide has been developed recently for wearable heating membranes. , In these studies, it was shown that graphene oxide layers give rise to a well-maintained network structure and that excellent thermal performance of such graphene-based micro–nanofibrous membranes can be achieved by optimizing the structure design and manufacturing strategy. Furthermore, thermoplastic elastomers such as polyurethane (PU), propylene-based elastomer (PBE), and styrene–ethylene/butylene–styrene copolymer have been used to fabricate elastic micro–nanofibrous membranes via the melt-blown process. , …”
Section: Introductionmentioning
confidence: 99%
“…23,24 In these studies, it was shown that graphene oxide layers give rise to a well-maintained network structure and that excellent thermal performance of such graphene-based micro−nanofibrous membranes can be achieved by optimizing the structure design and manufacturing strategy. Furthermore, thermoplastic elastomers such as polyurethane (PU), 25 propylene-based elastomer (PBE), 26 and styrene−ethylene/butylene−styrene copolymer 27 been used to fabricate elastic micro−nanofibrous membranes via the melt-blown process. 28,29 Despite such progress, current spinning methods are still limited to laboratory use because high costs arise by fabricating membranes that are distributed over the whole body.…”
Section: Introductionmentioning
confidence: 99%